2012
DOI: 10.1111/j.1475-2743.2012.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic‐C accumulation and N availability under improved pastures established in Mediterranean oak woodlands

Abstract: Long‐term effects of improved pasture establishment (with high proportion of legumes) on soil organic‐C status and N availability in Mediterranean cork oak (Quercus suber L.) woodlands were assessed. Soils were sampled beneath scattered crowns and in open areas, considering two systems: unmanaged and managed woodlands where improved pastures were installed 26 and 32 years ago. Total and labile C and N pools were measured and C and N mineralization were determined over 24 weeks laboratory incubation. Soils unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 43 publications
(73 reference statements)
6
26
0
4
Order By: Relevance
“…The high TOC observed in soil under oak canopies might be the result of the long-term transfer to the soil of high amounts of organic C deriving from the aboveground tree biomass (Moreno et al, 2007) and tree rhizodeposition (Pausch et al, 2013), as well as from dejections of grazing sheep that, particularly in the summer, rest in the shade under the tree canopies. According to what was observed by Gómez-Rey et al (2012), PAU showed a content of C 0 , MR basal , and MR higher than that in PAO, indicating a larger soil microbial activity and a positive trend for C stock potential. These findings might suggest, given the similar MBC values between PAO and PAU, the presence of 2 structurally distinct microbial communities in the open grassland or below the tree canopy.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The high TOC observed in soil under oak canopies might be the result of the long-term transfer to the soil of high amounts of organic C deriving from the aboveground tree biomass (Moreno et al, 2007) and tree rhizodeposition (Pausch et al, 2013), as well as from dejections of grazing sheep that, particularly in the summer, rest in the shade under the tree canopies. According to what was observed by Gómez-Rey et al (2012), PAU showed a content of C 0 , MR basal , and MR higher than that in PAO, indicating a larger soil microbial activity and a positive trend for C stock potential. These findings might suggest, given the similar MBC values between PAO and PAU, the presence of 2 structurally distinct microbial communities in the open grassland or below the tree canopy.…”
Section: Discussionmentioning
confidence: 93%
“…Accordingly, we chose to intensively study 1 site from each land use type rather than attempting to replicate sites across the ecosystem. Even though this experimental design was a case of "simple pseudoreplication" (Hurlbert, 1984), our approach has been considered valid to compare land uses in the same site (Lagomarsino et al, 2011) and for comparing between positions with respect to the tree crown projections (Almagro et al, 2009;Gómez-Rey et al, 2012).…”
Section: Soil Sampling and Storagementioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, three specific actions are suggested: (i) in all cases, grazing management should be adapted to increase the resilience of plant communities to climatic variability (Su 2007), (ii) special attention should be paid to the improvement of agro-silvo-pastoral systems (Gómez-Rey et al 2012), and (iii) natural margins should be considered due to their role in SOC sequestration (D'Acunto et al 2014;Francaviglia et al 2014). …”
Section: Livestock Integration Into Dryland Farming Systemsmentioning
confidence: 99%
“…Moreover, due to the short-term nature of this experiment, it is necessary to monitor the long-term effects. Some early studies have already provided positive results in this respect [32,33].…”
Section: The Effects Of Cultivated Pasture Establishment On Ecosystemmentioning
confidence: 96%